Epidemiological and etiological investigations of hand, foot, and mouth disease in Jiashan, northeastern Zhejiang Province, China, during 2016 to 2022 - Yuan, Yongjuan; Chen, Yun; Huang, Jian; Bao, Xiaoxia; Shen, Wei; Sun, Yi; Mao, Haiyan (Frontiers in Public Health, 2024)
Background: Hand, foot and mouth disease (HFMD) is a common infectious disease in children. Enterovirus A71 (EV71) and coxsackievirus A16 (CA16) have been identified as the predominant pathogens for several decades. In recent years, coxsackievirus A6 (CA6) and coxsackievirus A10 (CA10) have played increasingly important roles in a series of HFMD outbreaks. We performed a retrospective analysis of the epidemiology of HFMD and the spectrum of different viral serotypes, to elucidate the genetic and phylogenetic characteristics of the main serotypes in the Jiashan area during 2016 to 2022. Methods: Descriptive epidemiological methods were used to analyze the time and population distribution of HFMD in Jiashan during 2016 to 2022 based on surveillance data. Molecular diagnostic methods were performed to identify the viral serotypes and etiological characteristics of HFMD. Phylogenetic analyses was based on VP1 region of CA16 and CA6. Results: The average annual incidence rate of HFMD fluctuated from 2016 to 2022. Children aged 1-5 years accounted for 81.65% of cases and boys were more frequently affected than girls. Except when HFMD was affected by the COVID-19 epidemic in 2020 and 2022, epidemics usually peak in June to July, followed by a small secondary peak from October to December and a decline in February. Urban areas had a high average incidence and rural areas had the lowest. Among 560 sample collected in Jiashan, 472 (84.29%) were positive for enterovirus. The most frequently identified serotypes were CA6 (296, 52.86%), CA16 (102, 18.21%), EV71 (16, 2.86%), CA10 (14, 2.50%) and other enteroviruses (44, 7.86%). There were 71 and 142 VP1 sequences from CA16 and CA6, respectively. Substitution of N218D, A220L and V251I was detected in CA16 and may have been related to viral infectivity. Phylogenetic analysis showed that CA16 could be assigned to two genogroups, B1a and B1b, while all the CA6 sequences belonged to the D3a genogroup. Conclusion: CA6 and CA16 were the two major serotypes of enteroviruses circulating in the Jiashan area during 2016 to 2022. Continuous and comprehensive surveillance for HFMD is needed to better understand and evaluate the prevalence and evolution of the associated pathogens.